Dual Graphitic‐N Doping in a Six‐Membered C‐Ring of Graphene‐Analogous Particles Enables an Efficient Electrocatalyst for the Hydrogen Evolution Reaction. Issue 47 (7th October 2019) - Lin, Zhiyu; Yang, Yang; Li, Mengsi; Huang, Hao; Hu, Wei; Cheng, Ling; Yan, Wensheng; Yu, Zhiwu; Mao, Kaitian; Xia, Guoliang; Lu, Jian; Jiang, Peng; et al.
Abstract: Graphene‐based materials still exhibit poor electrocatalytic activities for the hydrogen evolution reaction (HER) although they are considered to be the most promising electrocatalysts. We fabricated a graphene‐analogous material displaying exceptional activity towards the HER under acidic conditions with an overpotential (57 mV at 10 mA cm −2 ) and Tafel slope (44.6 mV dec −1 ) superior to previously reported graphene‐based materials, and even comparable to the state‐of‐the art Pt/C catalyst. X‐ray absorption near‐edge structure (XANES) and solid‐state NMR studies reveal that the distinct feature of its structure is dual graphitic‐N doping in a six‐membered carbon ring. Density functional theory (DFT) calculations show that the unique doped structure is beneficial for the activation of C−H bonds and to make the carbon atom bonded to two graphitic N atoms an active site for the HER. Abstract : That material is dope ! Graphene‐analogous particles with dual graphitic‐N doping in a six‐membered carbon ring are successfully prepared. Infrared spectroscopy, synchrotron‐based X‐ray absorption spectroscopy, and solid‐state NMR spectroscopy are applied to study its structure and mechanism in the hydrogen evolution reaction, where a current density of 10 mA cm −2 is achieved at an overpotential of 57 mV.